2014
DOI: 10.1007/s00429-014-0717-9
|View full text |Cite
|
Sign up to set email alerts
|

A mu–delta opioid receptor brain atlas reveals neuronal co-occurrence in subcortical networks

Abstract: Opioid receptors are G protein-coupled receptors (GPCRs) that modulate brain function at all levels of neural integration, including autonomic, sensory, emotional and cognitive processing. Mu (MOR) and delta (DOR) opioid receptors functionally interact in vivo, but whether interactions occur at circuitry, cellular or molecular levels remains unsolved. To challenge the hypothesis of MOR/DOR heteromerization in the brain, we generated redMOR/greenDOR double knock-in mice and report dual receptor mapping througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
271
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(315 citation statements)
references
References 61 publications
25
271
2
3
Order By: Relevance
“…1B], whereas neither nor-BNI [KOR antagonist; main effect of treatment, F (1, 14) = 2.6, P = 0.131; Fig. 1C] nor naltrindole [DOR antagonist; main effect of treatment, F (1,14) = 0.5, P = 0.502; Fig. 1D] altered sodium intake.…”
Section: Mor Signaling Is Primarily Responsible For Endogenous Opioidmentioning
confidence: 98%
See 2 more Smart Citations
“…1B], whereas neither nor-BNI [KOR antagonist; main effect of treatment, F (1, 14) = 2.6, P = 0.131; Fig. 1C] nor naltrindole [DOR antagonist; main effect of treatment, F (1,14) = 0.5, P = 0.502; Fig. 1D] altered sodium intake.…”
Section: Mor Signaling Is Primarily Responsible For Endogenous Opioidmentioning
confidence: 98%
“…The nonselective opioid receptor antagonist naltrexone reduced the cumulative amount of sodium consumed by sodium-depleted mice [main effect of treatment, F (1,14) = 75.3, P < 0.001; Fig. 1 A and F for normalized 120-min totals].…”
Section: Mor Signaling Is Primarily Responsible For Endogenous Opioidmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recent study, double knock-in mice expressing the MOR and d-opioid receptor (DOR) fused in frame to mCherry and enhanced green fluorescent protein (eGFP), respectively, showed colocalization of these receptors in the midbrain and hindbrain (Erbs et al, 2015). Coimmunoprecipitation using anti-mCherry and anti-eGFP antibodies revealed that MORmCherry and DOR-eGFP belong to the same complex in the hippocampus from these mice, which confirms earlier detection of these MOR-DOR complexes in this brain region using a heteromer-specific antibody (Gupta et al, 2010).…”
Section: Detection Of Gpcr Dimers and Oligomers In Native Tissuesmentioning
confidence: 99%
“…Sans en être le seul substrat, les systèmes dopaminergiques jouent un rôle important dans la dépendance aux opiacés et, depuis 1992 et les travaux fondateurs de Johnson et North [2], un modèle dit de désinhibition a été décrit afin d'expliquer ce recrutement des systèmes dopaminergiques mésencéphaliques. Dans ce modèle, les opiacés Vignette (Photo © Sébastien Granier).semblable entre les espèces de mammifères, il existe néanmoins quelques différences interspécifiques dans cette distribution ainsi que dans les niveaux d'expression entre les structures cérébrales [15][16][17][18]. Ces récepteurs sont toutefois présents, à des niveaux modérés, dans la VTA de tous les mammifères qui ont été étudiés.…”
unclassified